Influence of hydrogel, irrigation and nutrient levels on wheat productivity - meena, raj pal (Journal of Cereal Research, 2015)
An investigation was conducted for two consecutive Rabi seasons of 2011-12 and 2012-13 at Research Farm of Indian Institute of Wheat & Barley Research, Karnal (Haryana) to study the effect of hydrogel (synthetic Poly Acryl Amid) on in situ moisture conservation under different nutrient and irrigation levels. The experiment was conducted in split plot design with three main plot treatments (no irrigation, two irrigations and four irrigations) and six sub-plot treatments (100% NPK without hydrogel, 100% NPK with 2.5 kg/ha hydrogel, 100% NPK with 5 kg/ha hydrogel, 70% NPK without hydrogel, 70% NPK with 2.5 kg/ha hydrogel, 70% NPK with 5 kg/ha hydrogel). Progressive increase in wheat grain yield was recorded with every increment in irrigation level and 4 irrigations brought about significantly higher grain yield (44.82 q/ha) over no irrigation (32.37 q/ha) and two irrigations (42.03 q/ha). No yield improvement was observed with hydrogel application. The difference among various hydrogel treatments were found statistically at par. Â Grain yield was the highest under 100 % of recommended dose of NPK with (40.26 q/ha) and without (41.14 q/ha) hydrogel. On pooled basis 70% NPK application with and without hydrogel recorded significantly lower yield than 100% NPK application.